Experimental research of turbulator that stated on air inlet of gasoline engine on emission effect - Can, Ibrahim; Oner, Cengiz; Sugozu, Ilker (Sila Science, 2011)
In this study, the measuring performance and burning effects of petrol-driven engines with a tabulator in their air entrance have been investigated by experiments.With applied experiments specific fuel consumption and exhaust emissions are being measured by running the engines at different loads with and without a turbulator. As a result, engines that run at low circulations with a turbulator in their air entrance decrease fuel consumption whereas at high circulations due to cylinder inner pressure burning process begins too early in order not to delay firing to burn under high load and as a consequence generation of knocking is detected.
Keywords: Turbulator; Gasoline engine; Combustion; Emission